Pengaruh Metode Economic Value Added (EVA), Return On Asset (ROA), Return On Equity (ROE), dan Debt To Equity Ratio (DER) Terhadap Return Saham - Monica Faulina Fernandus; Indra Widjaja (Universitas Tarumanagara, 2020)
Performance measurement can be used to measure company's success in a certain period of time and can be used as input for improvement of the company in the future. In measuring company performance, investors usually see financial performance reflected in various ratios. Managerial work measurements rarely use value added calculation approach to the cost of invested capital. Because of the limitations and weaknesses of the ratio, EVA method emerged as a measure of company performance.This study aims to determine whether LQ45 companies in Indonesia have succeeded in adding value, so their performance is positive and which is the most significant performance evaluation methods: EVA, ROA, ROE, or DER. The research period is within 2016-2018 using Eviews 9.The results showed that although the companies are listed in the LQ45 category, the use of capital structure policies are not optimal and random effect method states DER as the most significant method for measuring company performance.